2010
DOI: 10.1042/bj20100517
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determination of selectivity of the site 3 modulator (BmK I) to sodium channels in the CNS: a clue to the importance of Nav1.6 in BmK I-induced neuronal hyperexcitability

Abstract: BmK I, a site-3-specific modulator of VGSCs (voltage-gated sodium channels) from the Chinese scorpion Buthus martensi Karsch, can induce spontaneous nociception and hyperalgesia and generate epileptiform responses in rats, which is attributed to the modulation of VGSCs in the neural system. However, which VGSC subtype is targeted by BmK I remains to be identified. Using two-electrode voltage-clamp recording, we studied the efficacy and selectivity of BmK I to three neuronal VGSCs co-expressed with the auxiliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…BmKM1 and OD1 are two examples tested for multiple channel isoforms, the former active on Na v 1.2, 1.3, 1.5, 1.6, and DmNa v 1 (32,43), and the latter affecting Na v 1.3, 1.5, 1.7, and DmNa v 1 (44,45). These two toxins were found to bind to the channels with differential affinities.…”
Section: Discussionmentioning
confidence: 99%
“…BmKM1 and OD1 are two examples tested for multiple channel isoforms, the former active on Na v 1.2, 1.3, 1.5, 1.6, and DmNa v 1 (32,43), and the latter affecting Na v 1.3, 1.5, 1.7, and DmNa v 1 (44,45). These two toxins were found to bind to the channels with differential affinities.…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of Na + currents in rat-cultured hippocampal neurons was prolonged significantly by BmK I while the inactivation time and the peak amplitude of the currents from Na v 1.2 channels expressed in Xenopus laevis oocytes were both increased by BmK aIV (Chai et al 2006). Na v 1.6, one of the major contributors to neuronal firing in central nerve system, was found to be significantly modulated by BmK I through amplifying the persistent currents and prolonging the inactivation time course (He et al 2010).…”
Section: Epileptogenesis/anticonvulsion Of Bmk Toxinsmentioning
confidence: 94%
“…Moreover, BmK I could also accelerate the slow inactivation development and delayed recovery through binding to Na v 1.6/b1 in the open state; Na v 1.2/b1 was less affected with only increased fast time constants of inactivating current upon the application of BmK I at high concentration (500nM); and Na v 1.3a/b1 was nearly insensitive (He et al 2010). Residue-swap analysis verified that an acidic residue (e.g., Asp1602 in mNa v 1.6) within the domain IV S3-S4 extracellular loop of VGSCs was crucial for the selectivity and modulation pattern of BmK I, which was in agreement with other a-scorpion toxins binding to sodium channels (Zuo and Ji 2004;Bosmans and Tytgat 2007).…”
Section: Pharmacological and Molecular Mechanisms Of Bmk Toxins Intermentioning
confidence: 97%
“…It was found that these toxins specifically bind to distinct regions on different VGSCs in either overlapped or separated forms, suggesting that binding sites on VGSCs are diverse (Jia et al, 1999;Li and Ji, 2000;Li et al, 2000aLi et al, , 2000bJi et al, 2002;Chai et al, 2006aChai et al, , 2006b. Also, key residues involved in toxin-channel inter-recognition or subtype-selective patterns were uncovered by site-directed mutagenesis (He et al, 2010(He et al, , 2011. These findings make BmK neurotoxins good candidates for probing the pharmacological and structural diversity of VGSCs in mammals or insects.…”
Section: Introductionmentioning
confidence: 95%